Effect of wildfires on tropical peatland vegetation in Meranti Islands District, Riau Province, Indonesia (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Silviana SH, Saharjo BH, Sutikno S. 2019. Effect of wildfires on tropical peatland vegetation in Meranti Islands District, Riau Province, Indonesia. Biodiversitas 20: 3056-3062. Wildfires are one of the main causes of forest destruction, disturbing forest sustainability. Wildfires are mainly caused by human activities, such as land clearing, wood harvesting, draining, etc. Wildfires could induce the loss of vegetation. This study was aimed at assessing the effect of wildfires on both vegetation biomass and necromass on coastal peatland ecosystems in Sungaitohor Village, Tebing Tinggi Timur Sub-district, Meranti Islands District, Riau Province, Indonesia. Analysis of vegetation and both above and below the ground biomass composition were performed. The approach used a paired sample with 4 replications (n = 4 burnt, n=4 unburnt). The variables observed in every research sites was analyzed using Student-T test. Models were generated and then validated to understand the effect of fires on biomass. The results showed that there was a significant difference in the studied parameters between the unburned area and burned area (P
Keywords: Biomass, burned peatlands, fire, necromass, unburned peatlands